Industrial Ecology Opportunities between CHP and Arable Farming in Alloa, Scotland - Whiting, Kai; Carmona, Luis Gabriel (Journal of Environmental Accounting and Management, 2026)
This paper addresses the potential for industrial ecology application at Alloa, Clackmannanshire, Scotland, between a consortium of arable farmers and a waste-to energy company. For improved onsite production, the average annual energy required to maintain the farmers’ proposed 3 ha greenhouse at optimal temperature (21°C during the day and 16°C at night) was calculated as 1448.8 MJ/m2. The coldest average temperatures, registered in February result in an energy requirement of around 3000 MJ/m2. The optimal quantity of carbon dioxide for the proposed glasshouse equates to 4032 kg of CO2 per day. In addition, the fertiliser produced by the waste-to-energy company will reduce the pesticide and chemical based nitrogen/potassium/phosphate demand. The authors identified that the heat, carbon dioxide and fertiliser produced at the proposed 10 MW CHP plant could be utilised by the consortium to produce higher quality food products in a symbiotic manner. The calculations undertaken indicate that the project is technically viable.